Case Report: Serial changes of ocular complications related to immune checkpoint inhibitors pembrolizumab and nivolumab - Cho, Wan-Hua; Chiang, Wei-Yu (Frontiers in Ophthalmology, 2023)
Background To demonstrate the rare ocular side effects in a patient receiving pembrolizumab and nivolumab for metastatic ovarian cancer. Case presentation A 37-year-old woman with recurrent metastatic ovarian cancer presented with blurred vision and photophobia after receiving pembrolizumab. Ocular findings were bilateral anterior chamber reactions, iris cysts, and macular flecks. Optical coherence tomography (OCT) indicated retinal pigment epithelium (RPE) and ellipsoid-band disruption. Her symptoms subsided with topical steroids but fundal appearance persisted despite cessation of immunotherapies. Similar episodes attacked again with multiple exudative subretinal fluid (SRF) developed after she received pembrolizumab and nivolumab. Steroids could cease anterior chamber reactions while SRF only subsided after discontinuation of immunotherapy. Extensive RPE and ellipsoid-band disruption remained without vision improvements. Conclusions We report a rare case of uveitis and retinopathy after immunotherapies with sequent pembrolizumab and nivolumab. A serial change of the maculopathy is demonstrated. Possible ocular toxicities during the treatment course should be considered, and the benefits of continuing the immunotherapy must be weighed against the risks.